1986
DOI: 10.1111/j.1469-8749.1986.tb03881.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Powered Mobility on Self‐initiated Behaviors of Very Young Children With Locomotor Disability

Abstract: SUMMARY This study reports the effects of powered mobility on the self‐initiated behavior of six children with various disabilities who, between 23 and 38 months of age, learnt to use motorized wheelchairs in less than three weeks. Using a multiple baseline design, two‐hour observation periods were videorecorded at 10‐day intervals before and after they achieved independent mobility. Frequency of self‐initiated interaction with objects, spatial exploration and communication with care‐giver were analyzed. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(89 citation statements)
references
References 6 publications
1
87
0
1
Order By: Relevance
“…It is suggested that by the age of 3 years, a sufficiently clear functional prognosis can be made and children could be subdivided into three treatment groups: (1) Those who by the age of 3 years have yet to achieve locomotion patterns which require adequate trunk control, will need the early supply of adequate assistive devices to enable them to develop assisted motor independence, generally a powered wheelchair (Butler 1986(Butler , 1997Bottos et al 1997Bottos et al , 1999b). This early independence is likely to help the neuropsychological maturation of the child who otherwise is limited by ineffective mobility and is often totally dependent on adults to move them about.…”
Section: Treatmentmentioning
confidence: 99%
“…It is suggested that by the age of 3 years, a sufficiently clear functional prognosis can be made and children could be subdivided into three treatment groups: (1) Those who by the age of 3 years have yet to achieve locomotion patterns which require adequate trunk control, will need the early supply of adequate assistive devices to enable them to develop assisted motor independence, generally a powered wheelchair (Butler 1986(Butler , 1997Bottos et al 1997Bottos et al , 1999b). This early independence is likely to help the neuropsychological maturation of the child who otherwise is limited by ineffective mobility and is often totally dependent on adults to move them about.…”
Section: Treatmentmentioning
confidence: 99%
“…Independent mobility is a key component in maintaining the physical and psychosocial health of an individual [1][2][3]. Psychologically, a decrease in mobility can lead to feelings of emotional loss, anxiety, depression, reduced self esteem, social isolation, stress, and fear of abandonment.…”
Section: Problem Statementmentioning
confidence: 99%
“…Nonambulatory, visually impaired people often lack the cognitive, visual, and motor skills required to safely maneuver a power wheelchair and are therefore often denied powered mobility as a result of concerns regarding the safety of the user and the environment [10,12]. Researchers from engineering and the clinical side have attempted to make powered mobility available to such populations without compromising the safety of the user and the environment [3,10,[13][14].…”
Section: Problem Statementmentioning
confidence: 99%
“…It can also adversely affect a person's psychosocial and emotional health and limit his or her educational and vocational opportunities. Physical impairment when combined with visual impairment furthers the loss of independent mobility [1][2][3]. In aging populations, physical impairment is often accompanied by visual impairment due to causes such as macular degeneration, cataracts, glaucoma, and diabetic retinopathy [1].…”
Section: Problem Statementmentioning
confidence: 99%